Tugu peringatan: Lambang penjajah atau memperingati pejuang? - Ahmad Sabri, Ahmad Zaharuddin Sani; Hassan, Hazman (2012)
Several year ago Malaysian ex-minister of Information, Datuk Seri Zainuddin Maidin has express his comfortless regarding the existence of memorial to remember communist fighter in Nilai memorial ground that had trigger national controversy. However, his statement had being criticised by those who are pro to the build of the memorial.To make it worst, recently, a senior leader of one of the opposition political party, openly declare one of the well-known terrorist, who is a member of the 4th Company, Malay Communist Party who is directly involve in attacking and killing policeman and their family in Bukit Kepong as one of the national hero.He also proclaimed that Dato' Onn Jaafar and Tunku Abdul Rahman cannot be called as national hero who bring into our independency since they could considered as British officer. Due to all these nonsenses, this paper try to dig out the truth behind all the sensational issues by using library research method. The main question that we tried to solve, is it true, the existence of communist memorial in Malaysia? What are the reason and rational behind it? Last but not least, are we really need to have a memorial to remember the “goodness” done by them who are really known as traitor to our nation.